ANALISIS KINERJA STAFF BANQUET SECTION DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN DI HOTEL SWISS BELL MALEOSAN MANADO - Bet El Lagarense; Sony Wijanarko (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
This study aimed to analyze, quantify and explain the effects of banquet section staff performance on service quality in Swissbell Maleosan hotel Manado. This study used observational techniques, surveys and interviews. Method of sampling was random sampling. The final results of this study were obtained using simple linear regression analysis calculation. After doing research we obtained a simple linear regression analysis with the equation Y = 50 + 0.3 X showing that each time there is an increment to the unit of variable X ( Banquet Staff Section Performance), there will be an increase in variable Y( Service Quality ) with a value of 50. For the determinant coefficient r2 = 0.36 or 36%. This suggests that the increase in service quality caused by Banquet Staff Section Performance is 36%. While 64% is caused by other factors not studied by the researchers such as equipment, lack of effective service system and the unavailability of food menu. Hotel Management of Swiss Bell Hotel Maleosan Manado must continue to improve the performance of banquet staff section to be positive as the above assessment can continue to survive and even grow.